2020
DOI: 10.3390/app10124090
|View full text |Cite
|
Sign up to set email alerts
|

Total Variation-Based Noise Reduction Image Processing Algorithm for Confocal Laser Scanning Microscopy Applied to Activity Assessment of Early Carious Lesions

Abstract: The confocal laser scanning microscopy (CLSM) system has been widely used to analyze early carious lesions with fluorescent ligands in dental imaging. This system can be used to examine the physiological condition of cellular colonization in the tooth structure. However, the undesirable noise in CLSM images hinders accurate activity assessment of early carious lesions. To address this limitation, a total variation (TV)-based noise reduction algorithm with good edge preservation was developed, and its applicabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The image processing technology was also used in the CPM field using digital images or UAVs of construction activities [22,23]. Point cloud data sets were similarly used to evaluate the progress in construction buildings through laser scanning technology [19,24]. However, researchers used more than one sensing technology for more robustness and better results; for example, a study conducted by [25] used more than one 3D sensing technology (UWB system and laser scanner).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The image processing technology was also used in the CPM field using digital images or UAVs of construction activities [22,23]. Point cloud data sets were similarly used to evaluate the progress in construction buildings through laser scanning technology [19,24]. However, researchers used more than one sensing technology for more robustness and better results; for example, a study conducted by [25] used more than one 3D sensing technology (UWB system and laser scanner).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Another study used a combination of RFID and laser scanning technology [26]. Other studies have used a fusion of image processing methods and laser scanners [24,[27][28][29].…”
Section: Previous Studiesmentioning
confidence: 99%
“…In addition, research by Seo K. et al confirmed that the TV algorithm greatly improved the image characteristics in the noise distribution in the frequency domain in X-ray images [ 29 ]. Recently, a study on the applicability of the TV algorithm to confocal laser scanning microscopy images was also conducted, and a quantitative analysis method of noise level for two color channels was also proposed [ 30 ]. However, there is little research in the nuclear medicine field, especially PET/MR images, that has been recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the application of noise reduction algorithms can aggravate the effect of this undesirable phenomenon [ 14 , 15 , 16 ]. Accordingly, noise reduction algorithms using the latest technologies, such as total variation, wavelet transform, deep-learning, and non-local means (NLM), have been proposed to minimize the blurring effect and selectively remove only noise [ 17 , 18 , 19 , 20 ]. Among the noise reduction algorithms mentioned above, the NLM algorithm is a known method that can smooth the pixel value inside the edge structure and maintain the high-frequency signal by calculating the intensity and distance of neighboring pixels [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%